Relationship between low ankle mobility and knee injuries: A systematic review (Research, Society and Development, 2023)
Introduction: The present study's primary objective was to transmit knowledge to different categories about the importance of ankle mobility and the prevention of future injuries to the knee joint. These joint injuries can cause difficulty in activities of daily living, such as: going down and upstairs, running, walking, squatting or kneeling and remaining seated for a long time. Objectives: To analyze whether there is a relationship between reduced ankle mobility and knee injuries. Methods: This work is a systematic review, as it is a careful investigation with the application of explicit and systematic search methods, critical evaluation and synthesis of selected information, synthesizing evidence related to a specific topic. Results: Within the studies, 100% of the articles indicate that low ankle mobility is a risk factor for knee injuries, 10% of the articles show that low ankle mobility is a factor that indicates that within sports the incidence of injuries to the knee joint is greater. Conclusion: In short, by crossing the relationships between ankle mobility and knee injuries recently studied, it is possible to draw conclusions that make it very clear that there is indeed a cause-and-effect relationship in the sense that the lower the ankle mobility the greater the chance of injury to the knee joint.